Synthesis, structure and SOD activity of Mn complexes with symmetric Schiff base ligands derived from pyridoxal. (14th December 2015) - Signorella, Sandra; Daier, Verónica; Ledesma, Gabriela; Palopoli, Claudia; Back, Davi Fernando; Lang, Ernesto S.; Kopp, Cristiéli Rossini; Ebani, Patrícia; Pereira, Mateus Brum; Giacomelli, Cristiano; Piquini, Paulo Cesar
Graphical abstract: Four structurally characterized manganese(III) complexes of ligands obtained by condensation of aliphatic diamines and pyridoxal were tested for superoxide dismutation showing good activity with IC50 values in the range of 1.22–2.15 M. Abstract: This study describes the synthesis, crystal structure and antioxidant activity of manganese(III) complexes with Schiff-base ligands obtained from condensation of pyridoxal with alkyl diamines: [Mn(pyr2 en)(H2 O)2 ]Cl·4H2 O, [Mn(pyr2 en)(H2 O)(CH3 OH)]Cl, [Mn(pyr2 pn)(H2 O)2 ]ClO4 and [Mn2 (pyr2 bn)3 ]·4H2 O, where H2 pyr2 en = 1, 2-bis(pyridoxylidenamino)ethane, H2 pyr2 pn = 1, 3-bis(pyridoxylidenamino)propane and H2 pyr2 bn = 1, 4-bis(pyridoxylidenamino)butane. The four complexes catalyze the dismutation of superoxide efficiently with IC50 values in the range of 1.22–2.15 μM, evaluated through the nitro blue tetrazolium photoreduction inhibition superoxide dismutase assay, in aqueous solution of pH 7.8. The length of the alkyl spacer in the diamine fragment plays a key role in the antioxidant activity of these complexes, with [Mn(pyr2 pn)(H2 O)2 ]ClO4 showing the lowest IC50 value.